Genome mining combined metabolic shunting and OSMAC strategy of an endophytic fungus leads to the production of diverse natural products - Qian Wei; Jian Bai; Daojiang Yan; Xiuqi Bao; Wenting Li; Bingyu Liu; Dan Zhang; Xiangbing Qi; Dequan Yu; Youcai Hu (Elsevier, 2021)
Endophytic fungi are promising producers of bioactive small molecules. Bioinformatic analysis of the genome of an endophytic fungus Penicillium dangeardii revealed 43 biosynthetic gene clusters, exhibited its strong ability to produce numbers of secondary metabolites. However, this strain mainly produce rubratoxins alone with high yield in varied culture conditions, suggested most gene clusters are silent. Efforts for mining the cryptic gene clusters in P. dangeardii, including epigenetic regulation and one-strain-many-compounds (OSMAC) approach were failed probably due to the high yield of rubratoxins. A metabolic shunting strategy by deleting the key gene for rubratoxins biosynthesis combining with optimization of culture condition successfully activated multiple silent genes encoding for other polyketide synthases (PKSs), and led to the trace compounds detectable. As a result, a total of 23 new compounds including azaphilone monomers, dimers, trimers with unprecedented polycyclic bridged heterocycle and spiral structures, as well as siderophores were identified. Some compounds showed significant cytotoxicities, anti-inflammatory or antioxidant activities. The attractive dual PKSs gene clusters for azaphilones biosynthesis were mined by bioinformatic analysis and overexpression of a pathway specific transcription factor. Our work therefor provides an efficient approach to mine the chemical diversity of endophytic fungi.